Deferred Action for Childhood Arrivals (DACA): Maximizing Impacts in Medical Education and Health Care - Aaron Garcia; Aaron Lapidus; Mario Lorenzana De Witt; John Jawiche; Maria Macias Lopez; Sunny Nakae; Hyacinth Mason (Association of American Medical Colleges, 2022)
Introduction Deferred Action for Childhood Arrivals (DACA) provides a path for individuals who are undocumented to join the physician workforce. Indeed, recipients of DACA can play an important role in addressing health inequities in medicine. Although DACA has been in place since 2012, many medical schools remain unaware of it or are hesitant to consider recipients for admission. In a similar vein, the premedical community, including those with DACA status, may be unaware of their eligibility and the steps necessary to pursue medicine. Further education and outreach are needed to achieve institutional policies conducive to the inclusion and success of those undocumented in medicine. Methods We created an hour-long workshop to empower learners with key knowledge relevant to DACA policy and its impact on medicine. We evaluated the workshop through pre- and postworkshop questionnaires assessing participant knowledge and attitudes based on the theory of planned behavior (TPB). Results A total of 112 participants engaged in our workshop. Ninety-one pretests and 61 posttests were completed by attendees. Data revealed a significant increase in performance on all knowledge-based and TPB questions, including intention to participate in future policy development. Moreover, participants reported appreciating the interactive nature of the session and expressed feelings of empowerment by their newfound knowledge base. Discussion This workshop provides a promising foundation from which conversations and progress regarding DACA-related medical education policy can begin. Specifically, the workshop engages participants in the process of identifying actionable steps for overcoming barriers to inclusion and support.